Factors affecting participation in charity sport events involving a low intensive physical activity. Issue 3 (6th September 2011) - Won, Doyeon; Park, Meungguk; Lee, Kwang-Yong; Chung, Jaeyong
This study was to investigate motivational and constraining factors that affect participants in charity sport events (CSEs) involving a low intense physical activity. For this study, responses were collected from participants (N = 247) in three MS Walk events. Results revealed that the most important motive was supporting the cause, followed by socialising with others, enjoying sports and getting benefits. Participants perceive a greater number of external constraints than internal constraints. In addition, the findings from multivariate analysis of variances revealed differences in motivational factors and future intentions based on participation types. Results also suggest that CSEs should consider the participants' demographic characteristics as a base for market segmentation.